Konstruksi Nilai Nasionalisme dalam Bait Sya’ir Tanpo Waton (Analisis Semiotik Model Ferdinand De Saussure) - M. Sabron Sukmanul Hakim (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Each song has its own message, both worldly and ukhrawi's message. This study aims to find out how the construction of the values of nationalism in the verse "syi'irtanpo waton". Semiotic analysis used in this research is Ferdinand De Saussure'ssemiotic which focuses on how a sign is seen from the linguistic or language side. Theresults of this study indicate that how a poem constructs the value of nationalism, in thiscase is shi'ir tanpo waton by KH Moh Nizam As Shofa. In his poetry there is a deepnationalism value including; it takes a clean heart and clear mind to form a pure natureof nationalism, promoting honesty and trustworthiness, understanding comprehensivelynationalism not half measures, helping each other in working, istiqomah and alwayscarrying out the commands of Allah SWT and the guidance of Rasulullah SAW.